Potencialidades e dificuldades interpessoais de universitários: estudo de caracterização - Ribeiro, Denize Campos; Bolsoni-Silva, Alessandra Turini [UNESP] (My University, 2011)
The interpersonal development can stimulate quality social relationship and promote people´s health. Interpersonal relationships are demanded by the university context, which requires the students to develop and to express socially skillful behaviors. However, diffi culties in interpersonal relationship in the university are common. Characterization studies can help the identifi cation of diffi culties and behavioral potentialities of students and promote effi cient trainings with college students This research aimed to: a) describe the prevalence of reports of university students who sought for psychological help, as the behavior called social skills, (b) identify the partners (family, boyfriend (a), friends, colleagues, teachers) with whom such responses are issued, (c) describe consequences reported by students that occur in the interaction with such parties. Data were obtained from semi structured interviews and IHS-Del Prette instrument. The interviews data were categorized by the analysis content and IHS-Del Prette data were computed according to concerning instructions. The outcomes describe potentialities and diffi culties that the students presented in relation to the social skills according to different aspects: university, work, love relationship, friends and family. The behaviors reported with higher frequency are related to speaking in public, talking to the partner about the relationship, speaking with friends and family members and fl irt. It was also observed that in all the categories the behaviors had as consequence more punishing than reinforcing events. The outcomes obtained of IHS-Del Prette found out that 50% of the sample showed [ok] poor social skills repertoire demanding training.

O desenvolvimento interpessoal pode estimular relações sociais de qualidade e promover a saúde das pessoas. Relacionamentos interpessoais são exigidos pelo contexto universitário, o qual requer que os estudantes desenvolvam e emitam comportamentos socialmente habilidosos. Entretanto, é comum haver di- fi culdades em relacionamentos interpessoais na universidade. Estudos de caracterização podem ajudar na identifi cação de difi culdades e de potencialidades comportamentais de estudantes e promover treinamentos efi cazes com universitários. A presente pesquisa [tem] teve por objetivos: a) descrever a prevalência do relato de universitários, que buscaram por atendimento psicológico, quanto a comportamentos denominados de habilidades sociais; (b) identifi car os interlocutores (família, namorado(a), amigos, colegas, professores) junto aos quais tais respostas são emitidas; (c) descrever conseqüências relatadas pelos universitários que ocorrem na interação com tais interlocutores. Os dados foram coletados através de entrevistas semi-estruturadas e do instrumento IHS-Del Prette, sendo que as entrevistas foram categorizadas através de análise de conteúdo e o IHS-Del Prette computado conforme instruções próprias. Os resultados descrevem potencialidades e difi culdades que os estudantes apresentaram em relação às habilidades sociais de acordo com diferentes contextos: faculdade, trabalho, namoro, amigos e família. Os comportamentos relatados em maior freqüência referem-se a falar em público, conversar em relacionamento amoroso, com amigos e familiares e paquerar. Constatou-se também que em todas as categorias os comportamentos tiveram por conseqüência mais eventos punitivos que reforçadores. Os resultados obtidos pelo IHS-Del Prette evidenciaram que 50% da amostra tinham repertório de habilidades sociais com indicação para treinamento.
Keywords: Social skills; Colleges; Behavioral therapy; Prevention; Evaluation; Habilidades sociais; Universitários; Terapia comportamental; Prevenção; Avaliação